2022
DOI: 10.1155/2022/6242062
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Effect of Online Instruction, Flipped Instruction, and Traditional Instruction on Developing Iranian EFL Learners’ Vocabulary Knowledge

Abstract: During the COVID-19 pandemic, using online and flipped instruction is the best alternative for traditional instruction. Therefore, this study compared the effects of three instructions, including online, flipped, and traditional, on improving Iranian EFL learners’ vocabulary knowledge. To do so, 90 Iranian intermediate EFL learners were selected among 119 students as the participants of this study. The target participants were randomly divided into three equal groups (online, flipped, and traditional). After t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…This corroborates previous studies, which posit that while learning vocabulary through traditional classroom instruction can be restrictive, online resources provide more accessible and engaging practices that can boost learner motivation for continued learning (Ali, 2018;Krishan et al, 2020;Tan & Goh, 2020). Learners' preference for web-based learning rather than traditional methods aligns with numerous past studies (e.g., Alhujaylan, 2021;Altiner, 2019;Bashori et al, 2021;Mundir et al, 2022). Moreover, the learners in this study possessed sufficient technological access, online skills, and interest in ubiquitous resources that should enable them to use and navigate a self-instructed WBLR efficiently, anywhere, at any time.…”
Section: Wantssupporting
confidence: 71%
See 1 more Smart Citation
“…This corroborates previous studies, which posit that while learning vocabulary through traditional classroom instruction can be restrictive, online resources provide more accessible and engaging practices that can boost learner motivation for continued learning (Ali, 2018;Krishan et al, 2020;Tan & Goh, 2020). Learners' preference for web-based learning rather than traditional methods aligns with numerous past studies (e.g., Alhujaylan, 2021;Altiner, 2019;Bashori et al, 2021;Mundir et al, 2022). Moreover, the learners in this study possessed sufficient technological access, online skills, and interest in ubiquitous resources that should enable them to use and navigate a self-instructed WBLR efficiently, anywhere, at any time.…”
Section: Wantssupporting
confidence: 71%
“…It can be utilised to carry out various learning activities, which can be integrated into a curriculum and thereby to supplement traditional courses. Mundir et al (2022) found that integrating online instruction is more effective than traditional instruction. Similarly, using online tools was found to be more enjoyable for students than traditional teaching methods; and it helps learners to retain words better (Poláková & Klímová, 2019).…”
Section: The Use Of Web-based Learningmentioning
confidence: 99%
“…There is a difference between planned online language teaching and the remote online instruction that became the norm during the Covid-19 pandemic in US higher education contexts. Online as well as blended language courses have been shown to be as effective as classroom instruction (Cubillos, 2007;Means et al, 2009;Peterson, 2021) and in some cases even led to stronger language outcomes in certain skill areas (Chenoweth & Murday, 2003;Chenoweth et al, 2006;Enkin & Mejías-Bikandi, 2017;Mundir et al, 2022). In traditional online language courses both instructors and students choose this delivery format.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In delivering the teaching and learning virtually, technology is often considered as the delivery method which requires constricted coordination across instructional, content, and technology teams (Mundir et al, 2022). Thus, the development of digital technology is noteworthy in the scope of education in the world, including in Indonesia, one of which is the e-learning-based method (Rahmawati et al, 2021).…”
Section: Introductionmentioning
confidence: 99%